The effect of salesperson’s expertise and salesperson’s likeability through trust mediation (Case study of PT. Bank Negara Indonesia (Persero) Tbk. Brawijaya Malang) - Oktavia, Riwidya Tri (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study focuses on the role of salesperson in increasingrepurchase intention through trust that formed between salespersonand customers. The purpose of this study is to determine the effectof salesperson's expertise and salesperson's likeability on trust andrepurchase intention. The sample of this study was BNI BrawijayaMalang's customers who received special services from thesalesperson (personal banking assistant - PBA) and had a minimumdeposit of IDR 500,000,000, - The sample in this study was includedin the purposive sampling category and amounted to 140 people.Data analysis through Partial Least Square (PLS) with version 3.0smartPLS. The results of this study indicate that salesperson'sexpertise has a significant effect on trust and repurchase intention,salesperson's likeability has a significant effect on trust but is notsignificant in repurchase intention. Trust acts as a partial mediationon the influence of salesperson's expertise on repurchase intention,but acts as a complete mediation on the influence of salesperson'slikeability on repurchase intention.